Growth Performance, Feed Utilization and Body Composition of Clarias gariepinus (Burchell 1822) Fed Marine Fish Viscera-based-diet in Earthen Ponds - OKE, Vincent; ABOU, YOUSSOUF; ADITE, ALPHONSE; KABRE, A. T. (My University, 2016)
A 90-days experiment was conducted to study the effect of replacement of fishmeal (FM) with marine fish viscera (MFV) meal on growth performance, body composition and production of Clarias gariepinus fingerlings (mean weight 11.3 ± 0.1 g). Diets were three isonitrogenous (43% crude protein) and isoenergetic (20 KJ/g) diets containing 0% (D0), 30% (D30) and 50% (D50) of MFV, as FM substitute. Diet D0, without MFV, acted as a control. All these diets were compared to the commercial diet coppens developed for C. gariepinus. No significantly differences were found in final weight (range: 220.94-234.1 g), weight gain (range: 1937.2-1971.7%), specific growth rate (range: 3.30-3.37%/day), protein efficiency ratio (range: 1.93-2.09) and annual production (range: 378.3-415.0 kg/are/year) of fish fed coppens diet, D0 and D30 (p>0.05). Fish fed D50 showed significantly lower growth and feed utilization performances (p˂0.05). Moisture and crude protein were similar among dietary treatments (p>0.05). Lipid deposition in fish significantly increased with MFV level in diets, whereas ash content decreased (p˂0.05). The study indicates that MFV meal can be used up to 30% in formulation fish feed for promotion of Clarias gariepinus rearing in rural areas.
Keywords: Clarias gariepinus; Fishmeal replacement; Marine fish; viscera; Growth; Earthen ponds